Increasing the Role of Work Discipline and Job Trainings on Employee Performance - Lili Sularmi; Cherly Stifanny (MBIA, 2021)
Management is the science and art of regulating the process of utilizing human resources and other sources effectively and efficiently to achieve a specific goal. PD CBJ must review the increasing role of Work Discipline and Training to achieve employee performance. This study was conducted empirically and is one of the company's essential internal components to improve its general performance by facing the challenges of industrial revolution 4.0. This study applies quantitative research methods. The data collection utilizes the form of using a survey method with a questionnaire device. This study's target population was 64 (sixty-four) employees at PD CBJ as same as obtaining the saturated sample. The verification analysis takes the inferential statistics to prove the hypothesis using the multiple regression analysis techniques. This yield gives empirical evidence to show that Work Discipline plays a role in improving Employee Performance at PD CBJ. In contrast, Training does not play a role in enhancing Employee Performance at PD CBJ. As a result, Work Discipline and Training have a high position in increasing Employee Performance at PD CBJ, with a 71.3 percent determination score.